Comparative genome analysis of the genus Shewanella unravels the association of key genetic traits with known and potential pathogenic lineages - Cerbino, Gabriela N.; Traglia, German M.; Ayala Nuñez, Teolincacihuatl; Parmeciano Di Noto, Gisela; Ramírez, María Soledad; Centrón, Daniela; Iriarte, Andrés; Quiroga, Cecilia (Frontiers in Microbiology, 2023)
Shewanella spp. are Gram-negative rods widely disseminated in aquatic niches that can also be found in human-associated environments. In recent years, reports of infections caused by these bacteria have increased significantly. Mobilome and resistome analysis of a few species showed that they are versatile; however, comprehensive comparative studies in the genus are lacking. Here, we analyzed the genetic traits of 144 genomes from Shewanella spp. isolates focusing on the mobilome, resistome, and virulome to establish their evolutionary relationship and detect unique features based on their genome content and habitat. Shewanella spp. showed a great diversity of mobile genetic elements (MGEs), most of them associated with monophyletic lineages of clinical isolates. Furthermore, 79/144 genomes encoded at least one antimicrobial resistant gene with their highest occurrence in clinical-related lineages. CRISPR-Cas systems, which confer immunity against MGEs, were found in 41 genomes being I-E and I-F the more frequent ones. Virulome analysis showed that all Shewanella spp. encoded different virulence genes (motility, quorum sensing, biofilm, adherence, etc.) that may confer adaptive advantages for survival against hosts. Our data revealed that key accessory genes are frequently found in two major clinical-related groups, which encompass the opportunistic pathogens Shewanella algae and Shewanella xiamenensis together with several other species. This work highlights the evolutionary nature of Shewanella spp. genomes, capable of acquiring different key genetic traits that contribute to their adaptation to different niches and facilitate the emergence of more resistant and virulent isolates that impact directly on human and animal health.